Electroencephalogram Analysis of Magnetic Stimulation at Different Acupoints - Yin, Ning; Wang, Ao-Xiang; Wang, Hai-Li (Frontiers in Neuroscience, 2022)
As a new type of acupoint stimulation method, magnetic stimulation has been applied in the effect and regulation mechanism research of acupoint stimulation because it is non-invasive and easy to quantify. This paper combines magnetic stimulation technology with electroencephalography to analyze the time-frequency and the brain functional network results elicited by magnetic stimulation at different acupoints. The EEG signals during magnetic stimulation at ST36, ST40 and GB37 were recorded respectivily. The time-frequency results showed that the magnetic stimulation at ST36 and ST40 on the Foot Yangming Stomach Meridian increased the energy in the left parietal lobe and the right central region, and the energy increased mainly in the theta and alpha bands. However, during the magnetic stimulation at GB37 on the Foot Shaoyang Gallbladder Meridian, the energy in the central region and the frontal lobe increased, and the energy increased mainly in the delta, theta and alpha bands. Moreover, the energy in the right parietal lobe decreased during magnetic stimulation at GB37. The results of brain functional network were also consistent with time-frequency results. The brain network connections of GB37 stimulation in the central region were significantly less than that of ST36 and ST40 (p<0.01). In addition, the connections between central region and frontal lobe and the connections between central region and parietal lobe of GB37 stimulation were significantly different from that of ST36 and ST40 (p<0.01). The above results indicate that ST36 and ST40 on the same meridian have similar effects on the brain, while GB37 on the other meridian has completely different effects from ST36 and ST40. These findings illustrate the relative specificity of acupoints from another perspective.